Dissecting the link between PD-1/PD-L1-based immunotherapy and cancer pain: mechanisms, research implications, and artificial intelligence perspectives - Marco Cascella; Brigida Miranda; Carmen Gagliardi; Lucia Santaniello; Milena Mottola; Alida Mancusi; Laura Ferrara; Federica Monaco; Francesca Gargano; Francesco Perri; Alessandro Ottaiano; Maurizio Capuozzo; et al. (Exploration of Immunology)
Cancer-related pain represents one of the most common complaints of cancer patients especially for those with advanced-stage of disease and/or bone metastases. More effective therapeutic strategies are needed not only to improve the survival of cancer patients but also to relieve cancer-related pain. In the last decade, immune checkpoint inhibitor (ICI)-based immunotherapy targeting programmed cell death-1 (PD-1) and its ligand 1 (PD-L1) has revolutionized cancer care. Beyond its anticancer role, PD-1/PD-L1 axis pathway is involved in many other physiological processes. PD-L1 expression is found in both malignant tissues and normal tissues including the dorsal root ganglion, and spinal cord. Through its interaction with PD-1, PD-L1 can modulate neuron excitability, leading to the suppression of inflammatory, neuropathic, and bone cancer pain. Therefore, since the intricate relationship between immunotherapy and pain should be largely dissected, this comprehensive review explores the complex relationship between PD-1/PD-L1-based immunotherapy and cancer-related pain. It delves into the potential mechanisms through which PD-1/PD-L1 immunotherapy might modulate pain pathways, including neuroinflammation, neuromodulation, opioid mechanisms, and bone processes. Understanding these mechanisms is crucial for developing future research directions in order to optimize pain management strategies in cancer patients. Finally, this article discusses the role of artificial intelligence (AI) in advancing research and clinical practice in this context. AI-based strategies, such as analyzing large datasets and creating predictive models, can identify patterns and correlations between PD-1/PD-L1 immunotherapy and pain. These tools can assist healthcare providers in tailoring treatment plans and pain management strategies to individual patients, ultimately improving outcomes and quality of life for those undergoing PD-1/PD-L1-based immunotherapy.